Scientific domain analysis of professional competences - Guerrero Chanduví, Dante A. (2013)
The emerging paradigm of skills has been studied from different disciplines, it has generated a broad universe of research literature regarding competences: work and executive competencies, but there is not necessarily exists a agreement among authors on the definition of the term. Through this paper we try to give an approximation of the intellectual structure of research in relation to professional competences with the aim of bringing to the reflection of the approaches and trends of this term, seeking to contribute to improving the work of professionals we act in this area in understanding implicit and explicit aspects of this term often shows subjective to the person. Using scientific domain analysis, new paradigm of information science, we study the set of publications in journals listed in the multidisciplinary databases: "Web of Science" and "Scopus" from 1950 to mid-2012. The maps generated using scientific visualization software "Citespace II" allow us to visualize the lines of research, specialties and trends of the professional competences where we can identify eight groups formed from characteristics and common research topics.